Penambahan Asam Sitrat terhadap Kualitas Tepung Pisang Batu - Rizkika Rizkika; Noviar Harun; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The use of citric acid in banana stone flour can play an important role in preventing various digestive tract problems. The purpose of this study was to obtain the best concentration of citric acid as a soaking material for the quality of the banana flour produced. This research was conducted experimentally using a completely randomized design with five treatments and three replications in order to obtain 15 experimental units. The treatments in this study were AS1 (citric acid concentration 0.5%), AS2 (citric acid concentration 1.5%), AS3 (citric acid concentration 2.5%), AS4 (citric acid concentration 3.5%) and AS5 (citric acid concentration 4.5%). Data were analyzed statistically using analysis of variance and continued with Duncan's Multiple Distance Test (DMRT) at the 5% level. The results showed that the concentration of citric acid had no significant effect on the moisture content and ash content of the stone banana flour, but had a significant effect on the total plate count, crude fiber as well as the color descriptive test results and overall assessment of the stone banana. The best treatment in this study was AS5 treatment (citric acid concentration 4.5%) produced a water content of 6.430%, ash content 1.496%, starch content 36.366%, total plate number 1.333 log CFU/g, crude fiber content 0.910%, with descriptions stone banana flour was yellowish-white in color, had a banana flavor, and overall panelists like it. Keywords : banana stone flour, citric acid and water